(untitled) (International journal of artificial intelligence, 2025)
This article discusses the role of educational technology in the development of creative thinking in teacher training, and the impact of the use of educational technology in developing professional skills to provide a high quality of education along with continuous updating of professional knowledge and skills illuminated.